The huntress the adventures, escapades, and triumphs of Alicia Patterson: aviatrix, sportswoman, journalist, publisher - Arlen, Alice 1940-2016; Arlen, Michael J. 1930- (Pantheon Books, 2016)
"The fascinating biography of the maverick newspaperwoman, equestrian, aviatrix and intrepid adventurer Alicia Patterson, which follows her exceptional exploits through the first half of the 20th century, from her troublemaking days as the middle child of complicated parents to her successes as publisher of the Pulitzer Prize winning Newsday"...
Keywords: Patterson, Alicia -- 1906-1963; Newsday (Hempstead, N.Y.) -- History; BIOGRAPHY & AUTOBIOGRAPHY / General; BIOGRAPHY & AUTOBIOGRAPHY / Editors, Journalists, Publishers; BIOGRAPHY & AUTOBIOGRAPHY / Women; Frau; Geschichte; Women publishers -- United States -- Biography; Women journalists -- United States -- Biography; Women air pilots -- United States -- Biography; Women adventurers -- United States -- Biography; Horsemen and horsewomen -- United States -- Biography; Geschlechtergeschichte; Journalismus; USA; Biografie